PENGARUH MANAJEMEN TALENTA DAN KOMPETENSI TERHADAP KINERJA DIPLOMAT DALAM MISI DIPLOMASI EKONOMI DI KEMENTERIAN LUAR NEGERI REPUBLIK INDONESIA - Wahyu Caesar, Yureta; Suaedi, Falih (CV. Lafadz Jaya, 2024)
Improving human resource quality is a fundamental requirement for organizations in today's global era. Organizations are challenged to continuously enhance employee abilities, both in terms of talent and knowledge, to create employees with the necessary competencies. This study aims to explain the influence of talent management and competencies on diplomat performance, focusing on economic diplomacy missions within a government institution. The research adopts a quantitative approach with descriptive and inferential statistical design. The study was conducted at the Ministry of Foreign Affairs of the Republic of Indonesia. The independent variables are talent management and competencies, while the dependent variable is diplomat performance. The population includes all diplomats serving at Indonesian overseas missions, with a sample of 87 respondents. Data analysis was performed using Partial Least Square (PLS) with the help of Smart PLS version 3.7.7. The results show that talent management and competencies positively and significantly influence diplomat performance. Competencies have a more dominant influence on diplomat performance in economic diplomacy missions than talent management.